The Effect of The Solar Heat Flux to The Optimized Solar Chimney Power Plant: An Experimental Study - Hery Mada Indra Paska; Adhika Widyaparaga; F Fauzun; Abrar Ridwan; Ridwan Abdurrahman (Journal of Mechanical Design and Testing, 2020)
The Solar Chimney Power Plant (SCPP) is an energy conversion system that would absorb solar thermal energy and convert heat air into electrical energy using a collector. The main disadvantage of the  SCPP is that low efficiency because less solar heat flux can be converted to the electrical power affected by the design of the SCPP. This study was designed the SCPP by theoretical calculation for producing electrical power and experimented by designing the SCPP use a chimney with divergent shape, a collector with convergent shape, a turbine generator with 3 blades, and coating some materials at the collector’s ground to increasing the electrical power. The purpose of this work was to study about the impact of the solar heat flux ( ) to the temperature of air, to the velocity of air, to the power electricity and compare between power generated from theoretical calculations design and the experiments result. The result showed that the SCPP with the optimized design affect the performance of the SCPP’s output power. The power generated in this experiment is 0.1 Watt. That value is greater than output power from theoretical calculations about 42.8% for the same input solar heat flux ( ) 1118 W/m2 both for theoritical and experimental.